Silkworm cocoon type aminated multi-walled carbon nanotube-paraffin photo-thermal conversion phase change composite material and preparation method thereof

By adopting a cocoon-based aminized multi-wall carbon nanotuba-paraffin composite material in phase-changing Phase variable composite materials are suitable for phase -changing energy storage fields.

CN119371938AActive Publication Date: 2025-01-28SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411493946.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing phase change materials have problems such as flammability, volume expansion, leakage, poor compatibility and poor thermal conductivity during the phase change process, which limits their application in the field of phase change energy storage.

Method used

Using a cocoon-type aminized multi-wall carbon nano-nanotuba-paraffin light thermal transformation phase change composite material, by mixing the amino-based multi-wall carbon nanotubes at the melting temperature at the melting temperature, it is filtered, washed, and dry to prepare for the possession. Good thermal conductivity and thermal stability composite material.

Benefits of technology

Achieved thermal conductivity, increase the heat transfer area, better circulation performance, higher thermal conductivity, and have good thermal stability and easy -to -apply granular phase -like phase -like composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371938A_ABST
    Figure CN119371938A_ABST
Patent Text Reader

Abstract

The invention provides a silkworm cocoon type aminated multi-walled carbon nanotube-paraffin photo-thermal conversion phase change composite material and a preparation method thereof. According to the prepared silkworm cocoon type aminated multi-walled carbon nanotube-paraffin photo-thermal conversion phase change composite material, the silkworm cocoon granular phase change composite material with the stable shape and the micron-level particle size can be prepared, the larger specific surface area is achieved, the heat conduction performance of the obtained phase change composite material is improved, the heat transfer area is increased, and the thermal conductivity of the phase change composite material is improved. The granular phase-change composite material has the advantages of better cycle performance, higher thermal conductivity and better thermal stability, and the granular phase-change composite material is more convenient to use, simple in preparation process and convenient to popularize and apply.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of phase change material heat storage, and specifically relates to a cocoon-type amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material and a preparation method thereof. Background Art

[0002] With the proposal of the "zero carbon" goal, sustainable development has gradually become a global consensus, and renewable energy is gradually replacing most fossil fuels. New renewable energy represented by solar energy is widely regarded as the most important renewable energy due to its significant advantages of being inexhaustible. However, the time and space mismatch problem of solar energy limits its development. Phase change materials can store and release a large amount of thermal energy during the phase change process and are considered to be ideal materials in the field of solar thermal conversion and heat storage.

[0003] Phase change materials (PCMs) are energy storage media that can store or release large amounts of energy at a nearly constant temperature during the melting or solidification process, achieving efficient energy utilization and thus reducing CO 2 Emissions. Common organic PCMs, such as paraffin (PW), polyethylene glycol (PEG), fatty acids, etc. are white substances. When sunlight shines on PCM, the light waves will be reflected, resulting in PCM's poor ability to capture sunlight. Therefore, photothermal conversion materials can be introduced into the field of phase change energy storage. Photothermal conversion materials refer to a class of materials that can convert light energy into thermal energy through their own photothermal conversion mechanism under illumination conditions. The photon capture ability and the design and thermophysical properties of thermal energy storage materials affect the photothermal conversion performance. By compounding photothermal conversion materials with phase change materials, the solar heat absorbed by the photothermal conversion materials can be stored in the phase change materials, achieving comprehensive properties such as high thermal storage capacity, excellent photothermal conversion performance and good thermal conductivity.

[0004] However, the flammability, volume expansion, leakage, compatibility, poor thermal conductivity and poor photothermal conversion performance of phase change materials during the phase change process are the main problems hindering the development of phase change materials. Extensive research is mainly focused on the new composite phase change materials of shape-stable PCM (ss-PCM). There are many composite methods for phase change thermal storage materials, the most common of which are blending method, impregnation method, micro / nanocapsule method, sol-gel method, porous adsorption method, intercalation method, etc.

[0005] Carbon nanotubes (CNTs) are widely used in the field of photothermal conversion due to their excellent photothermal conversion performance and high thermal conductivity. The thermal conductivity of multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs) are about 3000W / (m·K) and 2000W / (m·K), respectively. Adding carbon nanotubes to paraffin can form a nano-enhanced heat transfer phase change material with excellent heat transfer performance and good stability. However, there is contact thermal resistance between carbon nanotubes and between carbon nanotubes and paraffin. In the application process, they often encounter problems such as poor dispersibility and low stability, which limits their practical application in phase change energy storage.

[0006] Chen et al. (Electro-and photodriven phase change composites based on wax-infiltrated carbon nanotube sponges, ACS NANO, 2012, 6, 12, 10884-10892) disclosed an electrothermal and photothermal phase change composite material based on paraffin impregnated in porous, formable sponge-like carbon nanotubes, which is prepared by the following steps: first, carbon nanotubes are subjected to a chemical vapor deposition method to obtain a carbon nanotube sponge, which is collected after being formed on the inner wall of a reactor and then cut into rectangular blocks; paraffin is dissolved in dichloromethane to obtain a solution with a concentration of 0.03 g / mL, and then the paraffin solution is dripped on the rectangular carbon nanotube sponge, the paraffin solution is quickly absorbed by the porous carbon nanotube sponge, and then the solvent is volatilized in a low-pressure environment to form a dense solid PW-CNTs phase change composite material with a large volume shrinkage. Although a shape-stable phase-change composite material can be prepared by the above preparation method, the acquisition cost of sponge-like carbon nanotubes is high, the preparation process is difficult to control, and the bulk PW-CNTs phase-change composite material is not conducive to application. Summary of the invention

[0007] In view of the defects of the prior art, the object of the present invention is to provide a cocoon-type amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material with good thermal conductivity and good thermal stability and a preparation method thereof.

[0008] To achieve the above purpose, the solution adopted by the present invention is as follows:

[0009] In the first aspect, the present invention provides a cocoon-type amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material, which is a cocoon-type phase change composite material with disorderly wound amino-modified multi-walled carbon nanotubes as coating wires and phase change material as filling core material; the particle size of the cocoon-type phase change composite material is 1-50μm; in the cocoon-type phase change composite material, the mass ratio of amino-modified multi-walled carbon nanotubes to phase change material is 1:(2-6).

[0010] Preferably, the particle size of the cocoon-type phase change composite material is 1-25 μm; in the cocoon-type phase change composite material, the mass ratio of amino-modified multi-walled carbon nanotubes to phase change material is 1:(3-5).

[0011] Preferably, the thermal conductivity of the cocoon-type phase change composite material is 0.3-0.5 W / (m·K), and the phase change enthalpy value is between 11.3-193.0 J / g.

[0012] Preferably, the phase change material is selected from one or more of monohydric alcohol phase change materials, straight-chain alkane phase change materials, and fatty acid phase change materials; the monohydric alcohol phase change material is selected from one or more of dodecanol, tridecanol, tetradecanol, pentadecanol, and hexadecanol; the straight-chain alkane phase change material is selected from one or more of paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane, and n-eicosane; the fatty acid phase change material is selected from one or more of palmitic acid, stearic acid, lauric acid, myristic acid, and palmitic acid; preferably, the phase change material is paraffin.

[0013] In a second aspect, the present invention also provides a method for preparing the above-mentioned cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material, comprising the following steps:

[0014] Step (1), dissolving the aminated multi-walled carbon nanotubes in deionized water, and ultrasonically dispersing the water to obtain an aminated multi-walled carbon nanotube aqueous solution;

[0015] Step (2), melting the phase change material into a liquid at a melting temperature;

[0016] Step (3), adding the molten phase change material into the aqueous solution of amino-modified multi-walled carbon nanotubes at the same temperature, and stirring at high speed;

[0017] Step (4), after the reaction is completed, the mixture is filtered, washed and dried to obtain a cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material.

[0018] Preferably, in step (1), the diameter of the aminated multi-walled carbon nanotubes is 10-50 nm and the length is 10-20 μm; the aminated multi-walled carbon nanotubes are obtained by aminated modification of carboxylated multi-walled carbon nanotubes by diamines, and the diamines are selected from any one of ethylenediamine, hexamethylenediamine and hexamethylenediamine.

[0019] Preferably, in step (1), the mass ratio of the amino-modified multi-walled carbon nanotubes to the deionized water is 1:(100-200), and the ultrasonic dispersion is performed for 1-2 hours.

[0020] Preferably, in step (2), the phase change material is selected from one or more of a monohydric alcohol phase change material, a straight-chain alkane phase change material, and a fatty acid phase change material; the monohydric alcohol phase change material is selected from one or more of dodecanol, tridecanol, tetradecanol, pentadecanol, and hexadecanol; the straight-chain alkane phase change material is selected from one or more of paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane, and n-eicosane; the fatty acid phase change material is selected from one or more of palmitic acid, stearic acid, lauric acid, myristic acid, and palmitic acid, preferably paraffin, with a melting temperature of 60-80°C.

[0021] Preferably, in step (3), the temperature when the two are mixed is 70-100°C, the volume ratio of the molten phase change material to the amino multi-walled carbon nanotube aqueous solution is 1:(20-60), the stirring speed of the high-speed stirring is 14000-18000rpm, and the stirring time is 5-10min.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The silkworm cocoon-type amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material prepared by the present invention can prepare a silkworm cocoon granular phase change composite material with a stable shape and a particle size at the micron level, and has a larger specific surface area. The obtained phase change composite material has improved thermal conductivity, increased heat transfer area, better cycle performance, higher thermal conductivity, and good thermal stability. Moreover, the granular phase change composite material is more convenient in use, has a simple preparation process, and is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a schematic diagram of the preparation process of the cocoon-type amino-modified multi-walled carbon nanotube-paraffin wax photothermal conversion phase change composite material.

[0025] Figure 2The DSC data of the phase change composite material prepared by different mass ratios of paraffin wax and amino multi-walled carbon nanotubes in the embodiment of the present invention. The instrument used was a Mettler-Toledo DSC3 differential scanning calorimeter (heating and cooling range 5-80°C, heating and cooling rate 5°C / min, N 2 Flow rate: 50mL / min)

[0026] Figure 3 The thermal conductivity test data of the phase change composite material prepared by different volume ratios of molten paraffin and carbon nanotube aqueous solution in the embodiment of the present invention. The instrument used is TCM, C-Therm thermal conductivity meter produced by Canada C-Therm Technology Co., Ltd. The thermal conductivity of the phase change composite material sample was tested at 25±0.5℃ (solid).

[0027] Figure 4 Schematic diagram (a) and SEM image (b) of the particle structure of the phase change composite material prepared under different case conditions in the embodiments of the present invention.

[0028] Figure 5 This is a DSC thermal cycle diagram of 50 times of the phase change composite material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.

[0030] The present invention provides a cocoon-type amino-modified multi-walled carbon nanotube-paraffin wax photothermal conversion phase change composite material, and the specific process of the preparation method thereof is as follows: Figure 1 As shown, the following steps are included:

[0031] Step 1: dissolving the aminated multi-walled carbon nanotubes in deionized water and performing ultrasonic dispersion to obtain an aminated multi-walled carbon nanotube aqueous solution.

[0032] In this step, the aminated multi-walled carbon nanotubes used in the present invention are carboxylated multi-walled carbon nanotubes subjected to amination modification by diamines, wherein the diamines include but are not limited to ethylenediamine, hexamethylenediamine, hexamethylenediamine and the like.

[0033] Taking the amination modification of carboxylated multi-walled carbon nanotubes with ethylenediamine as an example, the amination multi-walled carbon nanotubes used in the present invention can be prepared by the following steps: ultrasonically mixing carboxylated multi-walled carbon nanotubes MWCNTs-COOH, condensation agent DCC and ethylenediamine (EDA) for 30 minutes, and then heating in an oil bath at 120° C. for 24 hours; after the reaction is completed, ultrasonically washing away excess amine, DCC and by-products after the DCC reaction with anhydrous ethanol, filtering with a PTFE filter membrane, and vacuum drying the filtered carbon tubes at 60° C. for 24 hours to obtain amination carbon nanotubes.

[0034] The chemical reaction formula of MWCNTs-COOH and EDA is:

[0035] MWCNTs-COOH+NH 2 -CH 2 -CH 2 -NH 2 →MWCNT-CO-NH-CH 2 -CH 2 -NH 2

[0036] The prepared aminated carbon nanotubes have amino groups in the molecular formula that can be connected to the aminated carbon nanotubes in the form of covalent bonds with many chemical substances through an amination reaction, while the special structure of the carbon nanotubes themselves is not destroyed and the excellent properties they possess are still maintained. The amino groups they carry can also improve the hydrophilicity and polarity of the carbon nanotube surface, thereby improving the dispersibility and solubility of the carbon nanotubes, and making them have higher reactivity, and can be connected with a variety of metal ions and polymers in the form of amide bonds. In the present invention, the aminated multi-walled carbon nanotubes are directly mixed with the molten phase change material, and the amino groups on the aminated multi-walled carbon nanotubes can be firmly connected with the phase change material. Ultrasonic dispersion and high-speed stirring are used to help the aminated multi-walled carbon nanotubes be more completely and stably wrapped in the surface of the phase change monomer to form a shape-stable cocoon-type phase change composite material.

[0037] In this step, the mass ratio of the aminated multi-walled carbon nanotubes to deionized water is 1:(100-200), and ultrasonic dispersion is performed for 1-2 hours to obtain an aminated multi-walled carbon nanotube aqueous solution.

[0038] Step 2: Melting the phase change material into a liquid at a melting temperature.

[0039] In this step, the phase change material used in the present invention includes but is not limited to monohydric alcohol phase change material, linear alkane phase change material, fatty acid phase change material, etc. The monohydric alcohol phase change material includes but is not limited to dodecanol, tridecanol, tetradecanol, pentadecanol, hexadecanol, etc., the linear alkane phase change material includes but is not limited to paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane, n-eicosane, etc., the fatty acid phase change material includes but is not limited to palmitic acid, stearic acid, lauric acid, myristic acid, palmitic acid, etc. In the embodiment of the present invention, paraffin is used as an example, and its melting temperature is 60-80°C.

[0040] In some embodiments of the present invention, two or more phase change materials may be used as the core material of the microcapsule phase change material, for example, a mixture of n-octadecane and n-tetracosane as the core material, all of which are within the protection scope of the present invention.

[0041] Step 3: Add the molten phase change material into the aqueous solution of amino-modified multi-walled carbon nanotubes at the same temperature and stir at high speed.

[0042] In this step, the temperature of mixing the two should not be lower than the melting temperature of the phase change material, for example, it can be 70-100°C, the volume ratio of the molten phase change material to the amino multi-walled carbon nanotube aqueous solution can be 1: (20-60), the stirring speed of high-speed stirring can be 14000-18000rpm, and the stirring time can be 5-10min.

[0043] Step 4: After the reaction is completed, the product is filtered, washed and dried to obtain a cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material.

[0044] In this step, specifically: after the reaction is completed, the prepared sample is filtered, washed with 70° C. deionized water and 70° C. hot ethanol respectively, and the obtained product after filtration is placed in an oven at 60-80° C. and dried to constant weight.

[0045] The cocoon-type aminated multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material prepared by the preparation method of the present invention can simultaneously exert the phase change performance of the phase change monomer and the excellent photothermal conversion performance and high thermal conductivity of the aminated carbon nanotubes, and can prepare a cocoon granular phase change composite material (such as Figure 4 a), the particle size is in the micron level of 1-50 μm, and further, the particle size can be reduced to 1-25 μm. The preparation process of the present invention realizes a phase change composite material with a smaller particle size and a larger specific surface area. In the cocoon-type phase change composite material, the mass ratio of amino multi-walled carbon nanotubes to phase change material is 1: (2-6), and more preferably 1: (3-5). The obtained phase change composite material has improved thermal conductivity, increased heat transfer area, better cycle performance, higher thermal conductivity, and better thermal stability. Moreover, the granular phase change composite material is more convenient to use, the preparation process is simple, and it is easy to promote and apply.

[0046] The cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material provided by the present invention has important application prospects in many fields such as solar energy utilization, intelligent temperature control, electronic equipment heat dissipation and energy storage.

[0047] The present invention is further described below in conjunction with examples, the purpose of which is to better understand the content of the present invention and reflect the essential characteristics of the present invention, so the examples cited should not be regarded as limiting the scope of protection of the present invention. It is also particularly pointed out here that the specific experimental methods and equipment involved in the examples are conventional methods or implemented under the conditions recommended by the manufacturer's instructions unless otherwise specified, and the reagents involved are commercially available unless otherwise specified.

[0048] Embodiment 1:

[0049] In this embodiment, the mass of the amino-modified multi-walled carbon nanotubes is 1 g, and the mass of the paraffin is 6 g.

[0050] Place 1g of amino-modified multi-walled carbon nanotubes in 100-200ml of deionized water, and ultrasonically disperse for 1-2h to prepare an aqueous solution; add 6g of paraffin wax into a beaker and melt it at 60-80℃. When the two temperatures are the same, add the molten paraffin wax to the aqueous solution and stir it at 14000-18000rpm for 5-10min. Filter the obtained sample, wash it with 70℃ deionized water and 70℃ hot ethanol respectively, and then dry the obtained product in an oven at 60-80℃ to constant weight. Figure 2 It can be seen that the phase change enthalpy is 193.0±2.0 J / g.

[0051] Embodiment 2:

[0052] In this embodiment, the mass of the amino-modified multi-walled carbon nanotubes is 1 g, and the mass of the paraffin is 4 g.

[0053] Place 1g of amino-modified multi-walled carbon nanotubes in 100-200ml of deionized water and disperse them ultrasonically for 1-2h to prepare an aqueous solution; add 4g of paraffin wax to a beaker and melt it at 60-80℃. When the two temperatures are the same, add the molten paraffin wax to the aqueous solution and stir it at 14000-18000rpm for 5-10min. Filter the obtained sample and wash it with 70℃ deionized water and 70℃ hot ethanol respectively. After filtration, dry the obtained product in an oven at 60-80℃ to constant weight. Figure 2 It can be seen that the phase change enthalpy is 75.6±2.0 J / g.

[0054] Figure 5 This is a DSC thermal cycle diagram of 50 times of the phase change composite material prepared in Example 2 of the present invention. Figure 5 It can be seen that the phase change composite material prepared by the present invention still has excellent phase change performance after multiple cycles, indicating that the phase change composite material prepared by the present invention has good thermal stability and service life.

[0055] Embodiment 3:

[0056] In this embodiment, the mass of the amino-modified multi-walled carbon nanotubes is 1 g, and the mass of the paraffin is 2 g.

[0057] Place 1g of amino-modified multi-walled carbon nanotubes in 100-200ml of deionized water and disperse them ultrasonically for 1-2h to prepare an aqueous solution; add 2g of paraffin wax to a beaker and melt it at 60-80℃. When the two temperatures are the same, add the molten paraffin wax to the aqueous solution and stir it at 14000-18000rpm for 5-10min. Filter the obtained sample and wash it with 70℃ deionized water and 70℃ hot ethanol respectively. After filtration, dry the obtained product in an oven at 60-80℃ to constant weight. Figure 2 It can be seen that the phase change enthalpy is 11.3±2.0 J / g.

[0058] Embodiment 4:

[0059] In this embodiment, the volume of the molten paraffin is 5 ml, and the volume of the amino-treated carbon nanotube aqueous solution is 100 ml.

[0060] Place 1g of amino-modified multi-walled carbon nanotubes in 100ml of deionized water and disperse them ultrasonically for 1-2h to prepare an aqueous solution; add 4.5g of paraffin wax into a beaker and melt it at 60-80℃. When the two temperatures are the same, add the molten paraffin wax to the aqueous solution and stir it at 14000-18000rpm for 5-10min. Filter the obtained sample and wash it with 70℃ deionized water and 70℃ hot ethanol respectively. After filtration, dry the obtained product in an oven at 60-80℃ to constant weight. Figure 3 After testing and calculation, the thermal conductivity of the composite material is 0.30±0.01W / (m·K).

[0061] Embodiment 5:

[0062] In this embodiment, the volume of the molten paraffin is 3 ml, and the volume of the amino-treated carbon nanotube aqueous solution is 180 ml.

[0063] Place 1g of amino-modified multi-walled carbon nanotubes in 180ml of deionized water and disperse them ultrasonically for 1-2h to prepare an aqueous solution; add 2.7g of paraffin wax into a beaker and melt it at 60-80℃. When the two temperatures are the same, add the molten paraffin wax to the aqueous solution and stir it at 14000-18000rpm for 5-10min. Filter the obtained sample and wash it with 70℃ deionized water and 70℃ hot ethanol respectively. After filtration, dry the obtained product in an oven at 60-80℃ to constant weight. Figure 3 After testing and calculation, the thermal conductivity of the composite material is 0.50±0.01W / (m·K).

[0064] Figure 4b is a SEM image of the amino-modified multi-walled carbon nanotubes prepared in this example. It can be seen that the prepared amino-modified multi-walled carbon nanotubes are completely wrapped with paraffin wax to promote heat transfer.

[0065] Compared with Example 4, the thermal conductivity is increased by 67%, indicating that the thermal transfer performance of the amino-modified multi-walled carbon nanotubes prepared in Example 5 is significantly improved.

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A cocoon-type amino-modified multi-walled carbon nanotube-paraffin light-thermal conversion phase change composite material, characterized in that: The invention relates to a cocoon-type phase change composite material with disorderly wound amino multi-walled carbon nanotubes as coating wires and phase change material as filling core material; the particle size of the cocoon-type phase change composite material is 1-50 μm; in the cocoon-type phase change composite material, the mass ratio of amino multi-walled carbon nanotubes to phase change material is 1:(2-6).

2. The cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin light-thermal conversion phase change composite material according to claim 1, characterized in that: The particle size of the cocoon-type phase change composite material is 1-25 μm; in the cocoon-type phase change composite material, the mass ratio of the amino multi-walled carbon nanotubes to the phase change material is 1:(3-5).

3. The cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin light-thermal conversion phase change composite material according to claim 1, characterized in that: The thermal conductivity of the cocoon-type phase-change composite material is 0.3-0.5 W / (m·K), and the phase-change enthalpy value is between 11.3-193.0 J / g.

4. The cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin light-thermal conversion phase change composite material according to claim 1, characterized in that: The phase change material is selected from one or more of monohydric alcohol phase change materials, straight-chain alkane phase change materials, and fatty acid phase change materials. The monohydric alcohol phase change material is selected from one or more of dodecanol, tridecanol, tetradecanol, pentadecanol, and hexadecanol. The straight-chain alkane phase change material is selected from one or more of paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane, and n-eicosane. The fatty acid phase change material is selected from one or more of palmitic acid, stearic acid, lauric acid, myristic acid, and palmitic acid. Preferably, the phase change material is paraffin.

5. A method for preparing the cocoon-type amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material according to any one of claims 1 to 4, characterized in that: The steps include: Step (1), dissolving the aminated multi-walled carbon nanotubes in deionized water, and ultrasonically dispersing the water to obtain an aminated multi-walled carbon nanotube aqueous solution; Step (2), melting the phase change material into a liquid at a melting temperature; Step (3), adding the molten phase change material into the aqueous solution of amino-modified multi-walled carbon nanotubes at the same temperature, and stirring at high speed; Step (4), after the reaction is completed, the mixture is filtered, washed and dried to obtain a cocoon-shaped amino-modified multi-walled carbon nanotube-paraffin photothermal conversion phase change composite material.

6. The preparation method according to claim 5, characterized in that: In step (1), the diameter of the aminated multi-walled carbon nanotubes is 10-50 nm and the length is 10-20 μm; the aminated multi-walled carbon nanotubes are obtained by aminated modification of carboxylated multi-walled carbon nanotubes by diamines, and the diamines are selected from any one of ethylenediamine, hexamethylenediamine and hexamethylenediamine.

7. The preparation method according to claim 5, characterized in that: In step (1), the mass ratio of the amino-modified multi-walled carbon nanotubes to the deionized water is 1:(100-200), and ultrasonic dispersion is performed for 1-2 hours.

8. The preparation method according to claim 5, characterized in that: In step (2), the phase change material is selected from one or more of a monohydric alcohol phase change material, a straight-chain alkane phase change material, and a fatty acid phase change material. The monohydric alcohol phase change material is selected from one or more of dodecanol, tridecanol, tetradecanol, pentadecanol, and hexadecanol. The straight-chain alkane phase change material is selected from one or more of paraffin, n-pentadecane, n-hexadecane, n-heptadecane, n-octadecane, n-nonadecane, and n-eicosane. The fatty acid phase change material is selected from one or more of palmitic acid, stearic acid, lauric acid, myristic acid, and palmitic acid, preferably paraffin, with a melting temperature of 60-80°C.

9. The preparation method according to claim 5, characterized in that: In step (3), the temperature when the two are mixed is 70-100°C, the volume ratio of the molten phase change material to the amino multi-walled carbon nanotube aqueous solution is 1:(20-60), the stirring speed of the high-speed stirring is 14000-18000rpm, and the stirring time is 5-10min.

Citation Information

Patent Citations

  • Paraffinic based carbon nano-tube compound phase transformation heat accumulating material and preparation thereof

    CN101407714A

  • Preparation method of carbon nanotube modified composite microcapsule

    CN104069783A

  • Knittable multi-wall carbon nanometer modified composite phase change material and preparation method thereof

    CN108360082A

  • Preparation method of photothermal conversion phase-change energy storage composite material

    CN109096998A

  • Shaped phase change energy storage composite material and preparation method thereof

    CN110373161A